Effect of Dietary Intake of Lutein Rich Foods on the Retina and its Associated with Retinopathy Among Diabetic Patients - Hiba Raad Saeed; Ahmed Ghazi Dadoosh; Besmah Mohamad Ali; Khaled Awad Mohamed Elbassiouny (Diyala Journal of Medicine)
Background: Diabetic retinopathy (DR) is a common micro-vascular consequence of diabetes mellitus that affects the eyes. If untreated, DR cause damage to the retinal blood vessels and result in blindness or visual loss Hyperglycemia over long period of time results in increases inflammatory oxidative stress and protein kinase C pathways that eventually retinal capillary endothelial damage and pericyte loss occurred. Lutein is a carotenoid with anti-inflammatory and antioxidant properties.